Sports Psychology Skills and Moods in Peruvian Quadball (Quidditch) Players - Reyes-Bossio, Mario (2024)
The aim of the present work was to describe, compare by gender, and correlate the psychological sports skills and mood in Peruvian Quadball athletes (Quidditch). The sample was composed of 43 athletes belonging to the 6 clubs affiliated with the Peruvian Quadball Sports Federation (FDPQ). A total of 23% (n = 10) are female, 72% (n = 31) are male and 5% (n = 2) non-binary. Age ranges from 18 to 37 years with an average of 27 years (DT = 5.54). The Sport Performance Psychological Inventory (IPED) and Mood Questionnaire were used (BRUMS). The main results show that negative coping with moods had a positive correlation with confusion, anger, depression, and tension. Visual-imaginative control positively correlated with vigor, as did attitudinal control and vigor. There are no gender differences in psychological sports skills. It can be concluded that it is important to avoid negative coping due to its association with negative moods and its potential to adversely affect individuals’ emotional experiences. On the other hand, the moderate positive correlation between visual-imaginative control and vigor suggests that certain mental control strategies may be associated with higher levels of energy and vitality. Similarly, a moderate positive correlation was observed between attitudinal control and vigor, indicating that a positive and proactive attitude may be related to higher levels of vitality.